Effect of topical application of platelet‐rich plasma on chronic venous leg ulcerations. Issue 2 (6th December 2021) - Bossart, Simon; Seyed Jafari, S. Morteza; Lehmann, Mathias; Jossi‐Will, Andreas; Sane, Esther; Heidemeyer, Kristine; Schorno, Petra; Pelloni, Lorenzo; Rammlmair, Anna; Schlapbach, Christoph
Abstract: Wound products that reliably support healing of chronic leg ulcers remain a huge unmet need in clinical practice. Due to the lack of standardized comparable protocols and different systems for platelet‐rich plasma (PRP) preparation, there is limited data on healing rates in chronic venous ulcers. In our case series with a total of seven chronic leg ulcers in four patients, we investigated the healing rates based on standardized digital photographs of chronic venous ulcers after application of topical PRP using a digital imaging software. In 5 out of 7 ulcers, the PRP‐treated wound half showed faster healing as compared the control half of the wound. In this case series, PRP‐treated sides of chronic venous leg ulcers showed a tendency for accelerated healing as compared to nontreated collateral wound side. Our data support the evaluation of topical PRP treatment in the management of chronic venous leg ulcers.